Diversity of urban trees in International college of advanced technology Sarawak (ICATS) - Nurzaifah, binti Zainal Abidin (Universiti Malaysia Sarawak (UNIMAS), 2013)
Trees are an important urban resource and should be looked at as a critical piece of urban infrastructure. With effective planning and management, urban trees and forests will provide a wide range of important benefits to urbanites. International Colleague of Advanced Technology Sarawak (lCA TS) set up at Tabuan Jaya and is still under development or ongoing construction. There has not yet been a measured of Species Diversity:' The main aim of this project is to assess the diversity of trees in the ICA TS. The assessment is determined by calculating the number of tree species and diameter breast height (DBH) of each species. Species diversity index (SDI) of trees at ICATS is 9.48 and is considered relatively low. The 149 trees enumerated in the study area include 15 species. The most abundant species is Areca triandra species was dominant species contributing 23 individual trees. Samanea saman is the second as the most dominant species contributing 21 individual trees.